2021
DOI: 10.21037/jovs-20-93
|View full text |Cite
|
Sign up to set email alerts
|

Role of video-assisted thoracic surgery in T4 NSCLC

Abstract: For many years, T4 lung tumors have been considered less suitable for surgery, because of their local extension invading central structures or vertebral bodies. To date, many studies have confirmed the advantages in terms of survival of a multimodality approach made up of surgical resection associated with neoadjuvant and/or adjuvant therapy for selected patients with advanced lung cancer. In those patients, in fact, minimally invasive surgery could improve overall survival rates while promoting faster recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In skilled hands, UVATS has been shown to be a viable approach for advanced lung tumours. 2 A previous study demonstrated that advanced patients operated upon by VATS had similar results when compared with open surgery. 6 The successful execution of complicated UVATS lobectomy is dependent upon the expertise and experience gained through doing UVATS over time.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In skilled hands, UVATS has been shown to be a viable approach for advanced lung tumours. 2 A previous study demonstrated that advanced patients operated upon by VATS had similar results when compared with open surgery. 6 The successful execution of complicated UVATS lobectomy is dependent upon the expertise and experience gained through doing UVATS over time.…”
Section: Discussionmentioning
confidence: 97%
“… 9 , 10 VATS resection for large lung tumours is rarely undertaken or discussed because of adhesions, narrow spaces and the difficulty of moving the lobe, so it remains a difficult operation to undertake using a UVATS approach. 2 The difficulty associated with T4 lung cancer is related to the size of the tumour, which occupies the chest cavity, reduces the field of vision and requires more time to resect. Another difficulty is adhesion to the surrounding structures, which also takes more time and may cause more incidental injuries when compared with a smaller sized tumour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations